Knowledge of dentists in the capital of a northeastern Brazilian state on the use of chemical agents as adjuvants in periodontal therapy (Research, Society and Development, 2021)
Introduction: Dental biofilm is formed by the fixation and proliferation of bacteria in the acquired film existing on tooth surfaces and there is a direct relationship between the level of oral hygiene, quantity/quality of this biofilm and the prevalence of periodontal disease and its severity. However, the lack of proper brushing led to the search for chemical agents that would improve biofilm control. Objectives: To investigate the degree of knowledge of dentists about the use of these agents as adjuncts in periodontal therapy. Methodology: A questionnaire was applied to 164 dentists from the capital of a northeastern Brazilian state, containing questions such as: age, gender, academic degree, specialty, area of ​​expertise, form of professional updating and questions about chemical agents prescribed both in form of toothpaste and mouthwash. Results: Chlorhexidine was the preference of most respondents as for mouthwashes and Triclosan and Zinc Citrate were the most chosen substances for toothpastes. Conclusion: The knowledge about chemical agents as adjuvants in periodontal therapy by dentists proved to be limited, which may lead to incorrect prescriptions.